2022
DOI: 10.1590/1806-9282.20211197
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of related factors of behavioral problems in children with congenital pseudarthrosis of tibia

Abstract: This study selected 90 children with CPT, who were treated in Hunan Children's Hospital from August 2014 to August 2015, and their caregivers, as the research subjects. This study complied with the "Declaration of Helsinki of the World Medical Association" and was approved by the ethics committee of the hospital. All patients or their caregivers signed an informed consent form.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 16 publications
(14 reference statements)
0
1
0
Order By: Relevance
“…Based on this hypothesis, the fibrous hamartoma is resected completely during osteosynthesis. In past years it is observed that psychological changes along with their behavior after surgery influence patient post-op healing [ 34 ]. It is also seen that acceptance by society is an effective intervention for treating their psychological stress and anxiety [ 35 ].…”
Section: Reviewmentioning
confidence: 99%
“…Based on this hypothesis, the fibrous hamartoma is resected completely during osteosynthesis. In past years it is observed that psychological changes along with their behavior after surgery influence patient post-op healing [ 34 ]. It is also seen that acceptance by society is an effective intervention for treating their psychological stress and anxiety [ 35 ].…”
Section: Reviewmentioning
confidence: 99%